Novel mitral clipping technique overcoming extreme atrial dilatation. Issue 4 (4th December 2013) - Tiroch, Klaus; Vorpahl, Marc; Seyfarth, Melchior
<x xml:space="preserve">Abstract</x> The mitral clipping technique is emerging as a promising new treatment option for severe mitral regurgitation. The device was designed and assessed in intermediate risk populations, which is in contrast to the real world, where most patients are deemed to be at very high risk for open heart surgery. The cardiac anatomy of these patients often challenges the freedom grades of the current mitral clip device. In this case presentation, we describe a novel technique overcoming extreme atrial dilation in a patient with severe mitral regurgitation despite previous implantation of two mitral clips. Based on a low/anterior trans‐septal puncture, this procedure relied on a counter clock‐wise 90° turn of the steerable sheath and alignment of the clip delivery system to the mitral valve, thereby gaining additional longitudinal freedom. This resulted in the successful implantation of two additional clips with achievement of a mild to moderate mitral regurgitation without relevant gradient and dramatic and sustained clinical improvement of the patient. © 2013 Wiley Periodicals, Inc.